Unraveling the Mysteries of the Qur'an: Contemporary Challenges in Understanding the Power and Beauty of Qur'anic Language: Mengurai Misteri Al-Qur’an: Tantangan Kontemporer Dalam Memahami Kekuatan dan Keindahan Bahasa Al-Qur’an - Aidila, Tita; Saputri, Intan Rama; Hamida, Arla; Helmina, Helmina (Takwil: Journal of Quran and Hadith Studies, 2024)
The Qur'an, the holy book of Muslims, has been a source of wisdom and guidance for centuries. In the contemporary era, the challenge of understanding the power and beauty of Qur'anic language has never been more relevant. This article aims to unravel the mystery surrounding this sacred text, exploring how contemporary challenges arise in trying to understand and appreciate the Qur'an's linguistic uniqueness. This study uses qualitative methods. The qualitative method in this study is used to understand social phenomena in depth and detail. This method focuses more on interpretation and understanding the meaning of the data obtained, rather than measurement and hypothesis testing. The result of this study is the literary quality of the use of language in the Qur'an has a significant role in the spread of Islam among the Arab community in the seventh century, which gave birth to a special interest in the study of the Qur'an. Thus, the uniqueness of the Qur'anic language is known as Qur'anic Uslub or Stylistics. Based on several responses to the Qur'an, it can produce a unique phenomenon called “Quran in everyday life” in contemporary Qur'ānic discourse, reflecting how the Qur'an is responded to and understood beyond its textual meaning, through continuous interaction. Thus, the Qur'ān seems to come alive and merge with everyday life. The divine challenge in the Qur'ān refers to various verses that invite humans to contemplate and understand the signs of God's greatness in His creation. The implication is to encourage people to get closer to God, gain a deeper understanding of God, and take lessons from the signs in the universe. One of the verses that reflects the divine challenge is in Q.S Al-Baqarah verse 164.